KEPRIBADIAN WANITA JAWA DALAM SERAT SULUK RESIDRIYA DAN SERAT WULANG PUTRI KARYA PAKU BUWONO IX - Sri Harti Widyastuti (LITERA, 2014)
This study aims to describe Javanese women’s personality in the perspective of feminism and gender equality and inequality in Serat Suluk Residriya and Serat Wulang Putri. It employed the qualitative research design and modern philology. The findings are as follows. Javanese women’s personality in Serat Suluk Residriya includes their images. Gender inequality in Serat Suluk Residriya includes subordination, woman stereotype, rights to use but not to possess, women as sexual objects, and polygamy. Gender inequality in Serat Wulang Putri shows that women must have a lot of children. Gender equality in Sera Wulang Putrishows that men and women have equal rights to be ascetic, knowledgeable, skillful, brave and great, and wealthy.